"By Consequence and Implication only": Accusations and Defenses of Locke’s Christology from A Paraphrase and Notes on the Epistles of St. Paul - Kuhle, James (Locke Studies, 2025)
Throughout his life, John Locke came under heavy criticism for maintaining a Trinitarian-evasive posture in his theological writings. This led many over the past three centuries to regard the English philosopher as anti-Trinitarian, and more particularly, a Socinian. These heterodox charges primarily resulted from implications of his philosophical writings and a misunderstanding of his intentions in The Reasonableness of Christianity (1695), without paying much attention to his personal exegesis project, A Paraphrase and Notes on the Epistles of St. Paul (published posthumously between 1705-7). In both theological writings, Locke prioritizes irenicism and chooses not to directly address the Trinity. This article first surveys contemporary criticisms and defenses of Locke’s Christology with particular emphasis on the exchange between Dr. Winch Holdsworth and Catharine Trotter Cockburn as a microcosm of how Locke’s critics and supporters leveraged his silence for their arguments. Next, this article examines these charges of “Socinianism” as it pertains to Christology by comparing Locke’s treatments of widely recognized Trinitarian passages in Paraphrase with those of notable Trinitarians in seventeenth century England. Although it is clear from Paraphrase that he rejects a Socinian Christology, the Trinitarian-evasive Locke remains hesitant to reveal his Christological position. Instead, his comments establish the conditions for multiple Christological positions, once again underscoring his irenic priorities.